FAKTOR PENYEBAB DAN KEBIJAKAN PEMERINTAH PROVINSI DAERAH ISTIMEWA YOGYAKARTA MENGHAPUS KEMISKINAN Causes of Poverty and Yogyakarta Government Policy for Eradicating Poverty - Juli Panglima Saragih (Jurnal Ekonomi dan Studi Pembangunan, 2014)
In implementing policies to eradicate poverty in DI Yogyakarta within allocation of money, there is no decreasing of signifinact number of the poor in DI Yogyakarta until now. Both central and DI Yogyakarta governments have already been running some policies. Therefore, DI Yoyakarta government is needed to identify main factors that cause poverty faced by its people. Some of those factors are low of percapita income of people, people having no productive business, and less natural resources, as well. The result of analisys shows that low per capita income and regulation concerning on special region of Yogyakarta caused number of poor people. In future, Yogyakarta gorvenment should create new strategy of policies  such as increasing job creation, increasing and creating much business opportunities, other than aid money directly for the poors. Developing potential of local economic can hopefully increasing income per capita of the poors. Keywords: poverty, government policy, Yogyakarta Provincial Government.